(untitled) (Educational Knowledge, 2019)
Digital educational resources undeniably contribute to building inclusive educational communities, fostering positive learning environments for students through interaction, respecting individual learning paces and styles, promoting innovation, and promoting equality. This research aimed to analyze the digital educational resources proposed by the Chilean Ministry of Education for students with disabilities, from a mixed perspective encompassing technical, pedagogical, and accessibility aspects. The results reveal fundamental shortcomings, such as the unavailability of resources, pedagogical weaknesses, a focus primarily on permanent educational needs, a majority of foreign resources, and, most importantly, a lack of educational resources classified as high-quality.